DIFFERING PERSPECTIVES ON SCHOOL SEGREGATION ISSUES IN AMERICAN CHILDREN’S PICTURE BOOKS - Klęczaj-Siara, Ewa (Journal of Education Culture and Society, 2020)
Aim. School segregation is a common theme of children’s books on minority groups living in the United States. Although it is primarily associated with black-white racial divisions, currently it also concerns white-Latino or rich-poor disparities. The aim of this paper is to analyse children’s picture books featuring Latino and African American characters who participate in the struggle against school segregation. The authors of the books, being members of racial minorities themselves, offer differing perspectives on the problem. Although they criticise school segregation, they also focus on the white perspective and the reasons why integrating schools has always been hard to achieve.Methods. The study analyses the visual and verbal narratives of selected picture books using a variety of methods for examining this literary format. Among others, it applies the theory of picture book analysis by Martin Painter, William Moebius, Maria Nikolajeva and Carole Scott.Results. The article shows that despite the existing scholarship on race-related problems in American schools, children’s literature seems to be the medium which tries to explain the problem to youngsters being directly involved in the system of segregation.Conclusions. The results can be useful to educators who cope with the issue of racial diversity in American schools. They may consider using selected titles of children’s literature as teaching aids assisting students from minority groups in the process of self-development and empowerment.